Advances in Liquid Biopsy for Early Detection and Monitoring of Pancreatic Cancer - Rehman, Ubaid Ur; Rehman , Fiza; Quratulain Badar,; Falaq Shahid,; Adil Mohammad,; Syed Rizvan Ali, (Indus Journal of Bioscience Research, 2025)
Pancreatic cancer is a rather aggressive form of malignancy. It characteristically presents at an advanced stage and progresses aggressively. The liquid biopsy has revolutionized the diagnosis and monitoring approach. The present review provides details on current progress, clinical utility, and the challenge in applying the method for managing pancreatic cancer. These can shed light on tumor biology, molecular changes, and treatment responses with the examination of tumor-derived fluids like ctDNA, CTCs, and exosomes. Among the technologies which could enhance sensitivity and specificity to make this a more viable test for early detection and real-time monitoring are next-generation sequencing and microfluidics and other highly advanced exosome isolation techniques. Such clinical studies have only revealed recent times that liquid biopsy is indeed useful in the detection of hallmark mutations, such as KRAS and TP53, prognosis assessment, and therapeutic efficacy monitoring. Recent trends in multi-omics integration and artificial intelligence-driven biomarker discovery as well as liquid biopsy-based developing point-of-care diagnostic devices highlight the potential of revolutionizing personalized medicine. Despite its promise, some challenges that include low abundance of biomarkers, lack of standardization, and high costs characterize what limits acceptance of liquid biopsy in clinical practice. This review outlines the role which liquid biopsy can play in conquest of the challenges of diagnosis and therapy of pancreatic cancer. Concomitantly, it discusses future requirements for research, technological breakthroughs, and a collaborative attitude toward overcoming prevalent limitations. Multidisciplinary approaches in the fields of multi-omics, artificial intelligence, and scalable diagnostic tools hold the promise of enhanced early detection of pancreatic cancer and optimization of treatment strategies in the patients themselves.